Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 6306714 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "Geometry POLYGON((-91.054687 13.239945,-91.054687 -57.515822,-30.234375 -57.515822,-30.234375 13.239945,-91.054687 13.239945))", "HasGeospatialIssue is false", "BasisOfRecord is Specimen" ] } The dataset includes 6306714 records from 389 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0075149-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences